THE EFFECT OF LISTENING VOA SPECIAL ENGLISH ON THE SPEAKING COMPETENCEOF COMPUTER SCIENCESTUDENTS AT UNIVERSITAS LANCANG KUNING - Indah Muzdalifah (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
Technology now has become part of human life. In education, technology is as medium to support English Language Learning. One of this media is VOA Special English Education Report. This media is believed can increase students speaking skillin English. The problem is, how many times they should listening VOA Speacial Engish Education Report in order to improve their speaking English. Therefore, this research was aimed to find out whether the habitual of listening VOA Speacial English Education Report can improve the students‘ competence in Speaking Engllish. The sample of this research is ten students of Computer science . They were devided into two groups. Five students was asked to watch the VOA Special English Education Report everyday during three months continuously while another five students was asked to watch the VOA Special English once a week during three months. The result of this research, the speaking test of five students who watched the video everyday during two hours every week have better score rather than the students who wacthed the VOA Special Engish Education Report once a week during four hours. The method of this research is quallitative research. The data was collected by using scoring test which this score is purposed to describe the different significant score between two groups of students. Another data to support this research is the students activity note book during three months. Thus, the implication of this research that the habitual listening of VOA Specia English Education Report continuously can effect students‘ speaking skill in English especially in speaking.